The South Baghdad Electrical Station and its Environmental Impact on the Tigris River (Journal of the College of Education for Women, 2019)
The South Baghdad electrical station located on the eastern bank of the Tigris River south of Baghdad city was selected within the municipality of Karrada between two latitude ( 330 15 , 33 0 18 )North and longitude ( 44 0 27 , 44 030 ) East . The purpose of the study is to determine the contribution of the station to the effect of pollution of the Tigris water by taking water samples at the station site and two sites, one before and the other after the station, distributed over time periods of three months between each sample of water and the beginning of August and November Shabat and Mayar and analyzed water samples physically, chemically and biologically, It was found that the highest percentage of pollution was at the site of the station and the highest percentage of pollution was in August and reached (52.94) % as the contaminants that crossed the border were allthat turbidity and electrical conductivity and temperature and Chemical Oxygen Demandand Total Suspended Solids and Phenols and Biological Oxygen Deman and Total Plate Count and Fecal Coliform Bacteria, And then it was in November (47.05) % and represented by eachturbidity, electrical conductivity and Chemical Oxygen Demandand Total Suspended Solids and Phenols and Biological Oxygen Deman and Total Plate Count and Fecal Coliform Bacteria , The same percentage was in May (47.05) % turbidity and temperature and Chemical Oxygen Demandand Total Suspended